Kognisi Pengelolaan Limbah Plastik Terhadap Masyarakat Di Kecamatan Ciputat Kota Tangerang Selatan Sebagai Manifestasi Bela Negara - Aditama Candra; Fachri Fadillah; Ayu Diah; Ni Wayan Widya; Irma Abidahsari (Pascasarjana Universitas Jember, 2021)
This study focuses on the amount of plastic waste whuch piled up in Ciputat District, South Tangerang City. The purpose of this research is to show how ecobricks become a solution in dealing with these issues, by involving several parties as well as strategic steps in its implementation. The method used is observational research method or direct observation by looking at the facts in the field. The results of the study show that ecobricks have become a solution and ecobricks are in line with the United Nations Sustainable Development Goals (SDG's) Goals number 17. Parties that are involved in the implementation of SME and MSME ecobricks such as several Stakeholders from Ciputat District, South Tangerang City, and South Tangerang City Plastic Community. Moreover, the research is accompanied by strategic steps in implementing the implementation of ecobriks to deliver ideas in a proposal format to the Ciputat District office, cooperation by exchanging ideas between parties as well as guiding, monitoring and evaluating the research.